СИСТЕМА МОНИТОРИНГА ПРОИЗВОДСТВЕННЫХ ПОКАЗАТЕЛЕЙ ГПНТБ СО РАН (Библиосфера)
The author describes the stages of the development and implementation of the monitoring system for output indices in SPSTL SB RAS.